Effect of Instant Messaging Advertising on the Hierarchy‐of‐Effects Model Amid Teenagers in South Africa. Issue 1 (5th December 2017) - Duffett, Rodney G
Abstract: The rapid growth of social media has resulted in digital information and communications technology (ICT) channels for individuals, especially the youth, to connect with each other and the rest of their world. Consequently, instant messaging (IM), social network sites (SNS) and other mobile applications have become an integral part of life, as well as a daily destination for billions of young individuals, offering them a novel and instant means of communication in this interactive ICT space. The increase of social media adoption has captured the attention of marketers and consumers alike on a global scale, and with the fast changing communication environments, marketers now confront new challenges in terms of understanding consumer behavior, attitudinal responses and consumption patterns in the new millennium. However, there is a lack of research into young consumers' attitudes towards advertising on IM platforms in emerging nations. Mxit is the largest locally founded IM channel in South Africa (SA) and, hence, this inquiry examines the effect of IM (Mxit) advertising on the hierarchy‐of‐effect model attitude stages among teenagers in SA. The results of the investigations found favorable attitudes towards IM advertising among teenagers, which makes an important contribution to the deficiency of IM inquiry in developing economies. This study should also aid organizations and their brands to comprehend what makes teenagers develop positive attitudes as a result of IM advertising, thereby assisting with the improvement of promotion strategies on this expansive and predominantly mobile IM platform landscape in SA.